2002
DOI: 10.1063/1.1455135
|View full text |Cite
|
Sign up to set email alerts
|

An experimental setup for nondestructive deposition of size-selected clusters

Abstract: An experimental setup for the deposition of mass-selected clusters using a laser vaporization source and a magnetic field mass selector is presented. Nondestructive deposition and a coverage of 1% of a monolayer within 5 h are achieved for mass-selected metallofullerene clusters as demonstrated for deposited Ce@C 60 on highly oriented pyrolytic graphite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 36 publications
0
6
1
Order By: Relevance
“…The tendency to form large single clusters rather than distributions of smaller even-numbered ones-as observed in time-of-flight-mass spectra experiments 19,20 -could be related to the cluster density which is always superior to 1 per 10 6 Å 3 in our simulations, a value much larger than the experimental one of 1 per 10 8 Å 3 estimated by Yeretzian et al 21 Experimental evidence for the formation of large fullerene clusters can be found elsewhere. [21][22][23] It should be noted that our strong topological dependence on density rather than temperature does not agree with the results of Yamaguchi et al who used a tight binding molecular dynamics ͑TBMD͒ scheme and found a strong temperature influence on the topologies, but little influence of the density: for similar starting configurations at 1000 K, they obtained a density-independent mixture of sp and sp 2 structures consisting mainly of flat graphitic "flakes" connected by carbon chains.…”
Section: B Influence Of Temperature and Density On The Topology Of Tcontrasting
confidence: 49%
“…The tendency to form large single clusters rather than distributions of smaller even-numbered ones-as observed in time-of-flight-mass spectra experiments 19,20 -could be related to the cluster density which is always superior to 1 per 10 6 Å 3 in our simulations, a value much larger than the experimental one of 1 per 10 8 Å 3 estimated by Yeretzian et al 21 Experimental evidence for the formation of large fullerene clusters can be found elsewhere. [21][22][23] It should be noted that our strong topological dependence on density rather than temperature does not agree with the results of Yamaguchi et al who used a tight binding molecular dynamics ͑TBMD͒ scheme and found a strong temperature influence on the topologies, but little influence of the density: for similar starting configurations at 1000 K, they obtained a density-independent mixture of sp and sp 2 structures consisting mainly of flat graphitic "flakes" connected by carbon chains.…”
Section: B Influence Of Temperature and Density On The Topology Of Tcontrasting
confidence: 49%
“…The most prevalent continuous ionization sources used for ion soft landing include electron impact ionization (EI) (Pradeep et al, ; Biesecker et al, ; Wijesundara et al, ; Bottcher et al, ), electrospray ionization (ESI) (Feng et al, ; Ouyang et al, ; Alvarez et al, ; Volny & Turecek, ; Mazzei et al, ; Hamann et al, ; Hauptmann et al, ), direct current (DC) or radiofrequency (RF) magnetron sputtering combined with gas aggregation (Haberland et al, , , ; Barnes et al, ; Pratontep et al, ; Tanemura et al, ; Lim et al, ; Duffe et al, ; Watanabe & Isomura, ; Gracia‐Pinilla et al, ; Nielsen et al, ; Wepasnick et al, ; Hartmann et al, ; Ludwig & Moore, ; Yin et al, ), high energy ion sputtering (Lapack et al, ; Harbich et al, ; Dong et al, ; Bromann et al, ; Fedrigo et al, ; Schaffner et al, ; O'Shea et al, ; Yamaguchi et al, ; Lau et al, ), and gas condensation/aggregation (GC) (Patil et al, ; Goldby et al, ; Yoon et al, ; Baker et al, ). Soft landing has also been accomplished using various pulsed ionization methods including matrix‐assisted laser desorption ionization (MALDI) (Rader et al, ), laser ablation/vaporization (Honea et al, ; Messerli et al, ; Pauwels et al, ; Klingeler et al, ; Heiz & Bullock, ; Melinon et al, ; Kemper et al, ; Mitsui et al, ; Winans et al, ; Cattaneo et al, ; Kaden et al, ; Davila et al, ; Tournus et al, ; Wepasnick et al, ; Woodward et al, ), the pulsed arc cluster ion source (PACIS) (Siekmann et al, ; Kaiser et al, …”
Section: Overview Of Instrumentation For Soft Landing Of Ionsmentioning
confidence: 99%
“…Pulsed laser induced ionization, via both vaporization and desorption processes, has been coupled with mass analyzers for soft landing of mass‐selected ions. For example, laser vaporization sources (Dietz et al, ; Laaksonen et al, ; Russo et al, ; Duncan, ) have been coupled with quadrupole filters (Honea et al, ; Messerli et al, ; Nagaoka et al, ; Vučković, et al, ; Woodward et al, ), TOF analyzers (Gao et al, ), magnetic sector analyzers (Klingeler et al, ), and ion mobility spectrometers (Davila et al, ) to synthesize and select a variety of bare ionic clusters and charged nanoparticles for soft landing onto surfaces.…”
Section: Overview Of Instrumentation For Soft Landing Of Ionsmentioning
confidence: 99%
“…Different types of cluster sources [18][19][20][21][22][23][24][25][26] have been developed by several groups in the past. Most of the cluster sources exploit thermal evaporation, laser ablation, ion beam sputtering, magnetron sputtering, or discharges to evaporate the material for cluster production.…”
Section: Introductionmentioning
confidence: 99%